Politik Identitas dalam Hubungan Internasional: Bias Konstruksi Barat terhadap Ancaman Uji Coba Rudal Korea Utara dan India - Mohamad Rosyidin (Jurnal Transformasi Global, 2014)
Abstract             North Korea missile launch test had triggered widely international response particularly from the West. They sharply condemned North Korea that it destabilizes international security. Soon after that, India successfully launched ICBM which can load nuclear warhead. Contrast to North Korea, Western powers were silence over what had been done by India. This anomaly cannot be explained by realist that emphasize merely on material power. For realist, threat emerges from material capabilities. If realist were true, then Western power should have condemned both North Korean and India concerning missile launch test. Yet, the fact was not in accord with realist premise. This research seeks to explain the anomaly based on constructivist approach in International Relations. According to constructivist, threat derives from ideational structure rather than material capabilities. The central thesis of this research is that the contrast of Western powers response toward North Korea and India missile test is due to identity of both states perceived by the US. While North Korea is perceived as an ‘enemy’ because of its evil ideology, India is perceived as a ‘friend’ because of it shared democracy. Different conception of the identity lead to different conception of state interest and in turn lead to different act or policy.             Keywords: nuclear, proliferation, identity, ideology, democracy